MANHAJ TARJIH TENTANG SUNNAH/HADIS SEBAGAI SUMBER AJARAN ISLAM - Imron Rosyadi (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2020)
Muhammadiyah is an association founded by KH. Dahlan in 1430 H/November 18, 1912 AD in Yogyakarta. The birth of Muhammadiyah is a continuation of the reform movement in the Middle East. One of the organizational structures of Muhammadiyah is the Tarjih Council as a complete organization of Muhammadiyah. One of the characteristics of the renewal movement is the return to the Qur'an and as-Sunnah (ar-Ruju' ila al-Qur'an wa as-Sunnah). In Returning to as-Sunnah, Muhammadiyah has a manhaj. This paper tries to explain the views of the Tarjih Council on matters related to as-Sunnah as an authoritative source of Islamic teachings after the Qur'an. Not all as-Sunnah/hadith recorded in standard hadith books can be used as authoritative sources, they must meet certain criteria.